Sentiment Distribution and the Representation of Punk in Indonesian Mainstream Media - I Gusti Ngurah Aditia Tjandra Asmara; Muhammad Mustofa (Deviance Jurnal Kriminologi, 2026)
This study examines how Indonesian mainstream mass media construct representations of punk culture and how these representations are reflected in the distribution of news sentiment. Drawing on Cultural Criminology, media representation theory, and framing theory, the study compares patterns of representation in two influential Indonesian news institutions, Kompas.com and ANTARA News. Using quantitative content analysis and categorical data analysis, 221 online news articles published between 2015 and 2025 were collected and classified into positive, neutral, and negative sentiment categories. The findings show that negative sentiment dominates media representation of punk, accounting for 61.5% of all articles. Kompas.com demonstrates a stronger tendency toward negative representation, with 71.2%. Whereas ANTARA News presents a relatively more balanced pattern, including 43.9% positive reporting. Statistical analysis indicates a significant relationship between media type and sentiment distribution. Furthermore, Cramér’s V value indicates a small-to-moderate association, suggesting that differences in representation are systematically related to media institutions. While Kompas.com more frequently represents punk through narratives related to crime, public disorder, and law-enforcement intervention, ANTARA News provides comparatively greater visibility to narratives of empowerment, social inclusion, and community participation. These findings suggest that representation of punk varies across media institutions and that negative portrayals remain dominant in Indonesian news coverage. The study contributes to discussions on media representation, framing, and youth subcultures by providing empirical evidence of how different media institutions construct distinct understandings of the same subcultural phenomenon.